Burnout, Professional Self-Efficacy, and Life Satisfaction as Predictors of Job Performance in Health Care Workers: The Mediating Role of Work Engagement - Deisy Bernales-Turpo; Roy Quispe-Velasquez; Diony Flores-Ticona; Jacksaint Saintila; Percy G. Ruiz Mamani; Salomón Huancahuire-Vega; Mardel Morales-García; Wilter C. Morales-García (SAGE Publishing, 2022)
Background: It is essential to identify the factors that influence the work performance of health professionals working in health care facilities, especially in the context of the COVID-19 pandemic, since these factors have an impact on the quality of medical care provided to the population. Objective: This study aimed to analyze the mediating role of work engagement in the relationship between job burnout, professional self-efficacy, life satisfaction, and job performance in Peruvian health care workers. Methods: Cross-sectional explanatory study, with the voluntary participation of 508 health professionals (physicians and nurses) of both sexes (70.7% women, 29.3% men), and from different health facilities in the city of Lima. All participants were administered the Single Burnout Item questionnaire, the Professional Self-Efficacy Scale (AU-10), the Satisfaction with Life Scale (SWL), the Individual Work Performance Questionnaire (IWPQ), and the Utrecht Work Engagement Scale (UWES-9). Structural Equation Modeling (SEM) was used for data analysis. Results: In the SEM analysis, it was found that for the mediation model the incremental goodness-of-fit indices were significant (χ 2  = 2292.313, gl = 659, P  < .001, χ 2 /gl = 2.788). Career self-efficacy (β = .557, P  < .001) and life satisfaction (β = .289, P  < .001) were positive predictors of work engagement. While burnout was a negative predictor (β = .878, P  < .001). The consistent mediation of work engagement of professional self-efficacy, life satisfaction, and burnout had a positive predictor effect on job performance (β = .878, P  < .001). Conclusion: Research provides evidence that professional self-efficacy, life satisfaction, and burnout could influence job performance through work engagement.